2020
DOI: 10.1016/j.clnu.2019.02.028
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1, randomized double-blind, placebo controlled trial to evaluate safety and efficacy of epigallocatechin-3-gallate and cognitive training in adults with Fragile X syndrome

Abstract: Background & Aims: Despite the wide spectrum of experimental compounds tested in clinical trials, there is still no proven pharmacological treatment available for Fragile-X syndrome (FXS), since several targeted clinical trials with high expectations of success have failed to demonstrate significant improvements. Here we tested epigallocatechin-3-gallate (EGCG) as a treatment option for ameliorating core cognitive and behavioral features in FXS. Methods We conducted preclinical studies in Fmr1 knockout mice (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Several studies including animal, human, and cell cultures support the potential neuroprotective activities of green tea catechins against neurological disorders. Very recently, EGCG was found to be safe and potential in improving cognition using both preclinical (mice) and clinical (human) studies [68]. The concentrations of EGCG, which is the main and the most active component among catechins, are very low in human and rat plasma and EGCG disappears within several hours from systemic circulation (<8 h) due to fast and extensive metabolism (methylation, glucuronidation, and sulfation) and microbial metabolism and degradation, resulting in the formation of various microbial ring-fission metabolites, which are detectable (>8 h) in the plasma and urine [30,31,33].…”
Section: Conclusion and Future Expectationmentioning
confidence: 99%
“…Several studies including animal, human, and cell cultures support the potential neuroprotective activities of green tea catechins against neurological disorders. Very recently, EGCG was found to be safe and potential in improving cognition using both preclinical (mice) and clinical (human) studies [68]. The concentrations of EGCG, which is the main and the most active component among catechins, are very low in human and rat plasma and EGCG disappears within several hours from systemic circulation (<8 h) due to fast and extensive metabolism (methylation, glucuronidation, and sulfation) and microbial metabolism and degradation, resulting in the formation of various microbial ring-fission metabolites, which are detectable (>8 h) in the plasma and urine [30,31,33].…”
Section: Conclusion and Future Expectationmentioning
confidence: 99%
“…Furthermore, treatment with EGCG and glatiramer acetate in EAE mice delayed disease onset, reduced clinical disability and reduced inflammatory infiltrates ( 25 ). In clinical trials, oral intake of EGCG was associated with improved muscle metabolism during moderate exercise in RRMS ( 26 ) and improved cognitive rehabilitation in genetic disorders ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…In human clinical trials, green tea extracts and EGCG were shown to be safe for use in children and adults, including during prolonged periods (Kumar et al, 2016;de la Torre et al, 2020;Vilela et al, 2020), which reinforces the treatment potential of those components.…”
Section: Clinical Trials Involving Green Tea and Egcgmentioning
confidence: 64%
“…In a study conducted in 2012, EGCG (300 mg) improved neurological effects during alpha, beta, and theta brainwave stimulation, promoting, among other effects, increased calmness and reduced stress self-evaluated by healthy individuals over periods of 120 min (Scholey et al, 2012). These studies are corroborated by a more recent phase 1 trial conducted by de la Torre et al (2020). EGCG improved cognition and functional competence when combined with cognitive training during a 3-month follow-up (de la Torre et al, 2020).…”
Section: Clinical Trials Involving Green Tea and Egcgmentioning
confidence: 69%